Innovative Development of Telecommunications and Supply Chain Management in Kazakhstan - K. Maralov, Arman; A. Kirdasinova, Kasiya; Kurmanov, Nurlan; Kabdullina, Gulmira; Uandykova, Mafura (ExcelingTech, 2019)
In telecommunications, there are fundamental changes occurring around the world due to deregulation, new competition and fast innovation. The supply chain offers communication companies watching this change not to eat them the unused weapons to increase competitiveness. In modern conditions of socio-economic development of the Republic of Kazakhstan, one of the main areas is the development of the regional economy, in the context of which the most promising area is the telecommunications system and supply chain managment, since the level of competitiveness of local enterprises depends on the introduction of innovations into the global economy. This article provides a literature review of local and foreign authors who conducted research on the issues of innovative development of the Republic of Kazakhstan, including developmental patterns and characteristics of telecommunication systems and the strategies of supply chain management. An economic assessment of the current state as well as innovative development of telecommunications in Kazakhstan are given. As a result of the conducted research, the economic aspects of the research of the supply chain management in telecommunication sphere at the regional level were systematized, on the basis of which the relevant conclusions were made. In telecommunications, important functions of supply chain management are information synchronization and optimization of the management process. Synchronization means that information can be spread throughout the supply chain, while participants in the chain can keep pace with the changing demand.